Competitive federalism, individual autonomy, and citizen sovereignty - Viktor Vanberg (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2022)
[Conclusion] The principal aim of this paper is one of conceptual and theoretical clarification. Its purpose is to draw attention to the distinction between governments' functions as territorial enterprises and as club-enterprises, a distinction that tends to be ignored in contributions to the theory of competitive federalism even though it is of systematic relevance for the ways in which interjurisdictional competition unfolds. Adequately accounting, or failing to account, for the difference between the two functions, and the distinction between two kinds of exit, is bound to have significant consequences in practical politics. Yet, inquiring into its practical implications is only a secondary concern of the present paper. This issue is touched upon in the two preceding sections, about ambiguities in how the freedom-of-movement and nondiscrimination principles are interpreted in EU-legislation and by the European Court of Justice, and on requirements for a consistent system of taxation. His essay on the latter subject Schanz (1892:70) concludes on the note that a principle of taxation should meet two requirements. It ought to assign the liability to pay tax in the most appropriate manner and it should be expedient for the practical purposes of tax collection. The taxation principle sketched above can be claimed to assign the liability to pay tax in a more systematic and coherent manner than the taxation schemes that are commonly practiced. If implemented, this principle could surely not be undermined by interjurisdictional competition, yet, putting it into practice would pose the formidable challenge of orchestrating the transition from longaccustomed routines to yet to be discovered practices of tax collection that best approximate the systematic logic of the principle they are supposed to serve.
Keywords: 330